Análise da atenção secundária em odontologia no Estado de Minas Gerais - Patricia Azevedo Lino (2013)
This study aimed to describe and analyze specialized outpatient procedures in periodontics, endodontics and oral surgery performed in the State of Minas Gerais, 2010. Secondary data of the procedures performed in healthcare facilities and registered in the Information System of the Unified Health System. Descriptive and bivariate analysis was performed, considering p <0.05. 707,559 procedures were performed in 2,547 health units distributed in 693 (81%) counties in the State. Of these procedures, 55% are from the area of surgery, and 28% of periodontics and 17% are in endodontics. The units are predominantly public, under the municipal administration, 52.5% have some oral health team (OHT), 96.9% have no qualification as a Dental Specialty Centers (DSC). DSC are more efficient than the other units (p <0.001), but there is a significant percentage that does not meet the goals of the Ministry of Health. Municipalities that have DSC have higher population, more OHT, lower potential coverage and better HDI. A significant number of specialized procedures are performed in the state of Minas Gerais, especially in primary care settings. CEO establishments are more efficient than non-CEO, considering the average number of procedures. The minimum production goals are met by a minority of CEO.